Breast Lump Patterns Across Different Age Groups Among Female Patients Presenting to Surgical Outpatient Department of a Tertiary Care Hospital in District Malir Karachi: Breast Lump Patterns across Different Age Groups Among Female Patients - Gauhar, Tooba Mahmud; Mahmud, Tayyaba; Khanum, Rabia; Khan, Safi Ullah; Ahmed, Waqas; Jutt, Nazim (Pakistan Journal of Health Sciences, 2025)
The number of patients presenting with different types of breast lumps has been on the rise in the Malir district. Many females are being diagnosed with breast cancer. Objectives: To determine the pattern of breast lumps in different age groups in the outpatient department of Al-Tibri Medical College hospital in District Malir, Karachi. Methods: It was a descriptive cross-sectional study conducted at the Department of General Surgery, Al-Tibri Medical College Hospital, Karachi, from 1st November 2022 to 31st October 2024. Patients presenting in the Surgical Outpatient Department with breast lumps were included in the study. Age at presentation, symptoms, clinical features, investigations, biopsy reports, and operation notes (if operated) were recorded and submitted for analysis. Results: The commonest lesions were fibro-adenoma (33.6%), inclusion cyst of the breast (19%), and breast abscess (18.5%), followed by Carcinoma breast (17.7%). 51.7 % of cases were associated with pain. Among carcinomas, 43% presented with pain. The highest peak of presenting with malignant lesions was from 39 to 43 years, and 2nd peak was from 49 to 58 years. Most benign lesions presented between 24 to 28 years. The chi-square test showed a strong association between age range and pain (p-value<0.001), age range and type of lump (p-value <0.001), and marital status and type of lump (p-value<0.001). Conclusions: It was concluded that fibro-adenoma is the most common breast disease. Inflammatory lesions are also present frequently in the reproductive age group. Carcinoma breast presented in middle and later age groups, predominantly in married females in our district.